Differences in implicit motor learning between adults who do and do not stutter. (9th September 2022) - Höbler, Fiona; Bitan, Tali; Tremblay, Luc; De Nil, Luc
Abstract: Implicit learning allows us to acquire complex motor skills through repeated exposure to sensory cues and repetition of motor behaviours, without awareness or effort. Implicit learning is also critical to the incremental fine-tuning of the perceptual-motor system. To understand how implicit learning and associated domain-general learning processes may contribute to motor learning differences in people who stutter, we investigated implicit finger-sequencing skills in adults who do (AWS) and do not stutter (ANS) on an Alternating Serial Reaction Time task. Our results demonstrated that, while all participants showed evidence of significant sequence-specific learning in their speed of performance, male AWS were slower and made fewer sequence-specific learning gains than their ANS counterparts. Although there were no learning gains evident in accuracy of performance, AWS performed the implicit learning task more accurately than ANS, overall. These findings may have implications for sex-based differences in the experience of developmental stuttering, for the successful acquisition of complex motor skills during development by individuals who stutter, and for the updating and automatization of speech motor plans during the therapeutic process. Highlights: We investigated implicit motor learning in adults who stutter on the Alternating Serial Reaction Time (ASRT) task. The rate of implicit motor sequence learning is slower in male adults who stutter than in those who do not. The accuracy of general skill performance is better in adults who stutter. Amongst adults who stutter, working memory scores are predictive of general motor skill and sequence-specific performance. Differences in complex motor skill acquisition may influence proceduralization and automaticity of speech motor skills.